Kebutuhan layanan pendidikan khusus di sekolah dasar - Bahrudin Bahrudin; Indra Jaya; Cecep Kustandi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2021)
There is no real data on students who need special service education in elementary schools for the DKI Jakarta area. This study is interested in identifying and analyzing elementary school students who need special service education. This study will determine the real condition of the prevalence of the number of students in elementary schools who need special education services. The research method used is a quantitative approach. The instrument in this study used questions derived from the variable characteristics and characteristics of children with special needs. We collaborated with 14 elementary schools in the Thousand Islands, DKI Jakarta and the number of respondents in this study was 70 teachers. The data analysis technique was carried out by statistical analysis for quantitative. Therefore, the results obtained from a number of questions were asked to respondents and then transferred to the frequency distribution table. The results showed that the special needs most needed by students with special needs are slow learning, learning difficulties and intellectual disorders. The demand for educational services can increase family outreach efforts with schools through communication according to the types of needs of students. Inclusive school environments are ready to change and adapt and consider the needs of all people. The future research is required for an IQ test to ascertain special needs for intellectual disabilities and learning disabilities.